Design of voltage and current reference circuits on SOI-CMOS for high temperature applications - Quek, Michelle Wei-Ling (2014)
A CMOS bandgap reference that is able to operate at high temperature of up to 225oC is designed using XFAB 1μm technology. The designed output reference of 1.179V achieves a box model temperature coefficient of 14.625ppm/oC with a folded cascode amplifier and 17.5ppm/oC with a two-stage amplifier. The power supply rejection ratio is about 81dB and 82dB respectively. The bandgap reference employs the voltage mode approach to obtain the output reference voltage. The current reference circuit is created using the same bandgap circuit bootstrapped to the two-stage amplifier.